2018
DOI: 10.1055/a-0664-0733
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Mode-specific Responses to Eccentric Muscle Fatigue

Abstract: The primary purpose of the present investigation was to examine sex-related differences as a result of fatiguing eccentric muscle actions on torque, muscle blood flow, electromyography, and mechanomyography. Eighteen men and 18 women performed peak torque trials prior to (pretest), immediately after (posttest), and 5-min after (recovery) completing 50 submaximal (60% of eccentric peak torque), eccentric, isokinetic (180°·s ) muscle actions of the elbow flexors. Electromyographic and mechanomyographic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…However, physiological information is available in the periodograms to be used for muscle fatigue (Costa et al, 2010). Previous studies using bipolar and high-density EMG recordings found high variability in the chosen window length for analysis of isometric and dynamic contractions (Ament et al, 1993;Angelova et al, 2018;Cifrek et al, 2009Cifrek et al, , 2000do Espírito Santo et al, 2018;Falla et al, 2017;Guzmán-Venegas et al, 2015;Hawkes et al, 2018;Hegyi et al, 2019;Hill et al, 2018;Jordanic et al, 2016;Jordanić et al, 2017;Watanabe et al, 2018;Zhu et al, 2017). Most of these studies did not provide details about the windows overlap (do Espírito Santo et al, 2018;Hawkes et al, 2018;Hill et al, 2018;Lark et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physiological information is available in the periodograms to be used for muscle fatigue (Costa et al, 2010). Previous studies using bipolar and high-density EMG recordings found high variability in the chosen window length for analysis of isometric and dynamic contractions (Ament et al, 1993;Angelova et al, 2018;Cifrek et al, 2009Cifrek et al, , 2000do Espírito Santo et al, 2018;Falla et al, 2017;Guzmán-Venegas et al, 2015;Hawkes et al, 2018;Hegyi et al, 2019;Hill et al, 2018;Jordanic et al, 2016;Jordanić et al, 2017;Watanabe et al, 2018;Zhu et al, 2017). Most of these studies did not provide details about the windows overlap (do Espírito Santo et al, 2018;Hawkes et al, 2018;Hill et al, 2018;Lark et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using bipolar and high-density EMG recordings found high variability in the chosen window length for analysis of isometric and dynamic contractions (Ament et al, 1993;Angelova et al, 2018;Cifrek et al, 2009Cifrek et al, , 2000do Espírito Santo et al, 2018;Falla et al, 2017;Guzmán-Venegas et al, 2015;Hawkes et al, 2018;Hegyi et al, 2019;Hill et al, 2018;Jordanic et al, 2016;Jordanić et al, 2017;Watanabe et al, 2018;Zhu et al, 2017). Most of these studies did not provide details about the windows overlap (do Espírito Santo et al, 2018;Hawkes et al, 2018;Hill et al, 2018;Lark et al, 2019). Furthermore, the effects of window length and overlap have mainly been studied for isometric contractions (Xie and Wang, 2006;Zhang et al, 2010), but its effects remain unclear for dynamic muscle contractions.…”
Section: Introductionmentioning
confidence: 99%